Analysis of the relationship between the severity of road traffic crashes and the human factors involved: N4 Toll route case study - Gelderblom, Andries Johannes (Stellenbosch : Stellenbosch University, 2021)
Thesis (MEng)--Stellenbosch University, 2021.